Use of low-e glass in perovskite photovoltaic modules, the modules and methods of making the same

CN122846930APending Publication Date: 2026-09-29JIANGYIN JINGHAO NEW ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510331939.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

[0010]然而这些技术方案存在以下缺陷:首先,结构集成度低,Low-E玻璃和钙钛矿组件以独立部分形式通过胶粘和贴附的方式简单结合,不仅结合稳定性差,而且还增添了额外的复合/集成工艺;其次,材料和厚度增加:由于钙钛矿光伏组件本身已具有镀有ITO或FTO的玻璃作为透明导电电极,再叠加一层Low-E玻璃,结合后的结构相较于钙钛矿光伏组件自身会再多一层玻璃层,多层堆叠设计会导致整体厚度增加,且所需材料增多;最后,仍存在材料成本痛点问题:钙钛矿光伏组件的制造仍依赖于采用氧化铟锡(ITO)这种稀缺且昂贵的原材料作为透明电极,未能通过结构设计减少或替代铟基材料的使用,原材料成本居高不下

Benefits of technology

[0049](1)本发明中,采用导电Low-E玻璃作为透明导电电极层应用于钙钛矿光伏组件上,具备性能上的优势:利用Low-E玻璃本身良好的低辐射性能,以Low-E玻璃为基底载体,并以Low-E玻璃的镀银层直接作为衬底电极,具有导电性的Low-E玻璃在满足钙钛矿太阳能组件基本导电需求的同时,结构优化紧凑,制备和应用性能稳定,构成钙钛矿太阳能组件时,能有效阻挡室内外热量的传递,起到保温隔热的作用,保证使用安全,在炎热的夏季,可减少室外热量进入室内,降低室内空调制冷能耗;在寒冷的冬季,能阻止室内热量散失,减少供暖能耗,且导电Low-E玻璃与整个钙钛矿光伏组件的其他功能层兼容性良好,保证组件的稳定性能,长期使用不易出现性能衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122846930A_ABST
    Figure CN122846930A_ABST
Patent Text Reader

Abstract

This invention discloses the application of Low-E glass in perovskite photovoltaic modules, the module itself, and its fabrication method. It relates to the field of perovskite photovoltaic technology, utilizing conductive Low-E glass as a transparent conductive electrode layer in a perovskite photovoltaic module. The perovskite photovoltaic module comprises a composite conductive Low-E glass and a perovskite layer. The module fabrication method includes the following steps: performing P1 etching on a conductive Low-E glass substrate, wherein the spacing of the P1 etched lines is 4-8 mm and the width is 20-50 μm; ultrasonically cleaning and drying the substrate after P1 etching; fabricating a nickel oxide hole transport layer and a passivation layer; fabricating a perovskite thin film light-absorbing layer and a surface passivation layer; sequentially fabricating an electron transport layer, fabricating an interface buffer layer, P2 etching, fabricating an electrode layer, and P3 etching. This invention offers advantages such as optimized and compact structure, stable fabrication and application performance, reduced costs, simplified process flow, environmental friendliness, and green environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite photovoltaic technology, and in particular to the application of Low-E glass in perovskite photovoltaic modules, the module, and its preparation method. Background Technology

[0002] Photovoltaic modules, also known as solar panels, are the core component of a solar power generation system. They are primarily made of multiple individual solar cells connected in series and parallel, and then encapsulated to provide direct current (DC) output independently. The main function of photovoltaic modules is to convert solar energy into electrical energy, which can be stored in batteries or used to directly power loads. With continuous technological advancements and decreasing costs, the application prospects of photovoltaic modules in various fields will become even broader.

[0003] In the field of solar modules, perovskite solar modules have become a key area of ​​research and application due to their advantages of high photoelectric conversion efficiency, solution-processability, and relatively low cost. Integrating them with buildings can fully utilize building surface space to achieve building-based power generation, effectively reducing building energy consumption and showing extremely broad application prospects.

[0004] Transparent conductive electrodes are a crucial component in the fabrication of perovskite solar modules. While traditional indium tin oxide (ITO) transparent conductive electrodes possess excellent conductivity and transparency, they are commonly used in the fabrication of perovskite solar modules. However, indium resources are scarce and expensive, and their stability in high-temperature and humid environments is poor. These issues severely restrict the large-scale application and development of perovskite solar modules.

[0005] Low-E glass, or low-emissivity glass, is a product with multiple layers of metal or other compound films coated on its surface. It possesses high visible light transmittance and high mid-to-far-infrared reflectance, giving it superior heat insulation and light transmission compared to ordinary glass and traditional architectural coated glass. The emissivity of Low-E glass is significantly lower than that of ordinary glass, which typically has an emissivity of around 0.84, while Low-E glass can have an emissivity below 0.15 or even lower. This low emissivity characteristic makes Low-E glass excellent at thermal insulation, effectively reducing indoor heat loss and outdoor heat intrusion. Furthermore, Low-E glass also possesses a certain degree of electrical conductivity, primarily due to the metallic materials in the coating layers, especially the silver plating. Free electrons in the silver plating move directionally under the influence of an electric field, forming current paths and giving the glass surface conductivity. The conductivity, along with its heat insulation and light transmission properties, constitute the core advantages of Low-E glass in building energy conservation.

[0006] Conventional perovskite photovoltaic (PV) modules are fabricated on a transparent conductive substrate. This substrate is made by first depositing a layer of indium tin oxide (ITO) or fluorine-doped tin oxide (FTO) onto glass, and then fabricating the remaining parts of the PV module on this ITO or FTO-coated substrate. In this case, the perovskite PV module is a single, independent unit. However, when perovskite PV modules are used in building-integrated photovoltaics (BIPV) applications, such as combining them with Low-E glass (which offers good conductivity, low emissivity, and thermal insulation), the previously independent PV module must be separately integrated with the Low-E glass.

[0007] For example, a Chinese utility model patent with patent authorization announcement number CN 221807575 U discloses a power generation glass and curtain wall glass based on perovskite photovoltaic modules. The curtain wall glass includes a first glass layer, a first encapsulant layer, a perovskite photovoltaic module, a second encapsulant layer, and a second glass layer stacked sequentially from the outside to the inside. A high-transmittance Low-E film is attached to the inner side of the third glass layer. The Low-E film plays the role of blocking heat energy.

[0008] For example, a Chinese invention patent with publication number CN108625517 A discloses a new type of energy-saving power generation glass curtain wall based on transparent perovskite photovoltaic modules. The transparent perovskite photovoltaic modules are fixed to the back of Low-E glass by encapsulating adhesive, and the thermal insulation properties of Low-E glass provide a stable and good application environment for the perovskite photovoltaic modules.

[0009] The aforementioned existing technical solutions combine Low-E glass and perovskite photovoltaic modules, utilizing the thermal insulation properties of Low-E glass to provide protection for the perovskite modules.

[0010] However, these technical solutions have the following drawbacks: First, the structural integration is low. Low-E glass and perovskite modules are simply combined as independent parts through adhesive bonding and attachment, which not only results in poor bonding stability but also adds an extra composite / integration process. Second, the material and thickness increase: Since the perovskite photovoltaic module itself already has ITO or FTO-coated glass as a transparent conductive electrode, adding another layer of Low-E glass results in an additional glass layer compared to the perovskite photovoltaic module itself. This multi-layer stacking design leads to an increase in overall thickness and the amount of material required. Finally, the material cost issue remains: the manufacturing of perovskite photovoltaic modules still relies on the use of indium tin oxide (ITO), a scarce and expensive raw material, as a transparent electrode. The use of indium-based materials has not been reduced or replaced through structural design, resulting in high raw material costs. Summary of the Invention

[0011] The purpose of this invention is to address the shortcomings of existing technologies by proposing an application of Low-E glass in perovskite photovoltaic modules, the module itself, and its preparation method. Low-E glass is directly used as a transparent conductive electrode in perovskite photovoltaic modules, thereby reducing process steps, module thickness, and raw material usage, lowering raw material costs, overcoming the defects of traditional transparent conductive electrodes, and opening up a new path for the development of perovskite photovoltaic modules.

[0012] To achieve the above objectives, the present invention adopts the following technical solution:

[0013] The application of Low-E glass in perovskite photovoltaic modules: The conductive Low-E glass is used as a transparent conductive electrode layer in perovskite photovoltaic modules.

[0014] Furthermore, the perovskite photovoltaic modules are integrated into building-integrated applications.

[0015] A perovskite photovoltaic module includes conductive Low-E glass and a perovskite layer, wherein the conductive Low-E glass and the perovskite layer are compositely disposed, and the conductive Low-E glass serves as a transparent conductive electrode layer of the perovskite photovoltaic module.

[0016] Furthermore, the conductive Low-E glass has a silver plating layer, which serves as the battery electrode of the transparent conductive electrode layer on the perovskite photovoltaic module, and the sheet resistance of the silver plating layer is 0.9-2Ω / sq.

[0017] Furthermore, the conductive Low-E glass is double-silver or triple-silver Low-E glass, and the light transmittance of the conductive Low-E glass is 40%-70%.

[0018] Furthermore, the conductive Low-E glass also has an intermediate film layer;

[0019] The intermediate film layer is a composite stacked structure of dielectric layer / functional layer, wherein the stacking number and material thickness of the dielectric layer and the functional layer can be adjusted.

[0020] Furthermore, the perovskite photovoltaic module also includes a first charge transport layer, a second charge transport layer, a buffer layer, an electrode layer, and an outer protective layer, wherein the conductive Low-E glass, the first charge transport layer, the perovskite layer, the second charge transport layer, the buffer layer, the electrode layer, and the outer protective layer are sequentially stacked and composited.

[0021] Furthermore, when a self-cleaning glass structure is provided on one side of the perovskite photovoltaic module, a hollow layer is provided between the perovskite photovoltaic module and the self-cleaning glass structure, and the hollow layer is filled with an inert gas, wherein the self-cleaning glass structure is located on the side of the perovskite photovoltaic module away from the conductive Low-E glass.

[0022] A method for preparing a perovskite photovoltaic module, comprising the following steps:

[0023] Step 1) P1 etching is performed on a conductive Low-E glass substrate by laser scribing process, wherein the spacing of the P1 scribing lines is 4-8 mm and the width is 20-50 μm.

[0024] Step 2) Perform ultrasonic cleaning and drying on the substrate after P1 etching;

[0025] Step 3) Prepare the nickel oxide hole transport layer and passivation layer sequentially;

[0026] Step 4) Spin-coat the perovskite pre-liquid and anneal to form a perovskite thin film light-absorbing layer, followed by the preparation of a surface passivation layer;

[0027] Step 5) Prepare the electron transport layer;

[0028] Step 6) Prepare the interface buffer layer;

[0029] Step 7) Perform P2 etching using a laser scribing process;

[0030] Step 8) Prepare the electrode layer;

[0031] Step 9) Perform P3 etching using a laser scribing process.

[0032] Furthermore, in step 2), glass cleaner and deionized water are used for ultrasonic cleaning, and dry air is used for drying.

[0033] Furthermore,

[0034] In step 3), the nickel oxide hole transport layer is prepared by magnetron sputtering or solution method, with a thickness of 5-20 nm.

[0035] The solution method includes: spin-coating a NiOx dispersion onto a substrate that has been treated with ultraviolet ozone for 10-30 min. The spin-coating conditions are: low speed 500-1500 rpm for 3-10 s, high speed 3000-6000 rpm for 30-60 s, and annealing at 150-200℃ for 5-30 min.

[0036] The passivation layer is made of monolayer material or organic ammonium salt material. The 2PACz material is prepared by spin coating at a low speed of 3000-5000 rpm for 30-60 seconds and then annealing at 90-110℃ for 10-30 minutes.

[0037] Furthermore,

[0038] In step 4), the perovskite precursor solution contains PbI2, FAI, MAI, MACl, PbBr2, and PbCl2, and the solvent is a DMF / NMP mixed system or a DMF / DMSO system, dissolved at room temperature for 1-12 hours, with a concentration of 1.0-1.7M.

[0039] The spin coating parameters are 2000-5000 rpm, and 100-300 μL of chlorobenzene is added dropwise in the last 5-10 seconds. The annealing conditions are 100-150℃ for 5-30 min.

[0040] The surface passivation layer was prepared by spin coating. The materials were selected from organic salts, 2D materials, and small molecule materials. Among them, 2-thiophene ethyl ammonium chloride was prepared by spin coating at a low speed of 3000-5000 rpm for 30-60 seconds and then annealing at 100-130℃ for 3-10 minutes.

[0041] Furthermore, in step 5), the electron transport layer is prepared by vacuum thermal deposition of a fullerene C60 layer with a thickness of 10-50 nm, or by solution spin coating of a PCBM layer, with spin coating conditions of 5-20 mg / ml, rotation speed of 2500-4000 rpm, time of 30-60 s, and annealing at 70-120℃ for 5-30 min.

[0042] Furthermore, in step 6), the interface buffer layer is a BCP layer with a thickness of 5-20 nm prepared by vacuum deposition or a tin oxide layer with a thickness of 10-50 nm prepared by atomic deposition.

[0043] Furthermore, in step 8), the metal electrode layer is a 50-200nm Cu layer prepared by magnetron sputtering, wherein the semi-transparent electrode is a mixed layer of ITO and Cu with a total thickness of 50-200nm prepared by magnetron sputtering.

[0044] Furthermore,

[0045] The laser scribing processes in steps 1), 7), and 9) respectively employ near-infrared nanosecond laser / green picosecond laser, green picosecond laser, and green / ultraviolet picosecond laser.

[0046] The distance between the line P2 and P1 is 30-100μm, and the width is 40-100μm;

[0047] The distance between the line P3 and P2 is 30-100μm, and the width is 40-100μm.

[0048] Compared with the prior art, the beneficial effects of the present invention are:

[0049] (1) In this invention, conductive Low-E glass is used as a transparent conductive electrode layer in perovskite photovoltaic modules, which has performance advantages: Utilizing the good low-emissivity of Low-E glass itself, Low-E glass is used as a substrate carrier, and the silver plating layer of Low-E glass is used directly as the substrate electrode. The conductive Low-E glass meets the basic conductivity requirements of perovskite solar modules, while having an optimized and compact structure, stable preparation and application performance. When used to construct perovskite solar modules, it can effectively block the transfer of heat between indoors and outdoors, play a role in heat insulation, and ensure safe use. In the hot summer, it can reduce the amount of outdoor heat entering the room and reduce the energy consumption of indoor air conditioning. In the cold winter, it can prevent the loss of indoor heat and reduce the energy consumption of heating. Moreover, the conductive Low-E glass has good compatibility with other functional layers of the entire perovskite photovoltaic module, ensuring the stability of the module and making it less prone to performance degradation after long-term use.

[0050] (2) In this invention, conductive Low-E glass is used as a transparent conductive electrode layer in perovskite photovoltaic modules instead of indium tin oxide (ITO) as a transparent conductive electrode in the prior art. This has cost advantages: it avoids the large-scale use of expensive and scarce transparent conductive material such as indium tin oxide (ITO) in perovskite photovoltaic modules in the prior art, which greatly reduces the cost of raw materials; at the same time, it reduces the process steps of depositing additional transparent conductive electrodes, and also reduces the assembly and bonding operations between glass-ITO and other materials and low-E glass, which greatly simplifies the process flow, reduces equipment investment and energy consumption costs in the production process, and significantly reduces the overall manufacturing cost of the module.

[0051] (3) The present invention also has environmental advantages: by avoiding the large-scale use of the scarce metal indium, the environmental damage caused by the mining of indium ore is reduced, which plays a role in environmental protection; at the same time, in the production process, due to the simplification of the process steps, the amount of chemical reagents used and the generation of waste are reduced, which is in line with the green and environmentally friendly production concept; in the application of building integration, the building energy consumption is reduced, which indirectly reduces the carbon emissions generated by power generation, which has a positive significance for environmental protection. Attached Figure Description

[0052] Figure 1 This is a schematic diagram of the overall film layer of the perovskite photovoltaic module in Embodiment 1 of the present invention.

[0053] In the figure: 1. Conductive Low-E glass; 2. First charge transport layer; 3. Perovskite layer; 4. Second charge transport layer; 5. Buffer layer; 6. Electrode layer; 7. Outer protective layer. Detailed Implementation

[0054] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0055] Example 1

[0056] Perovskite photovoltaic modules, such as Figure 1 As shown, it includes conductive Low-E glass 1, a first charge transport layer 2, a perovskite layer 3, a second charge transport layer 4, a buffer layer 5, an electrode layer 6, and an outer protective layer 7, which are stacked and composited in sequence.

[0057] Among them, conductive Low-E glass 1 utilizes its inherent conductivity to directly serve as a transparent conductive electrode layer in perovskite photovoltaic modules. Conductive Low-E glass 1 exhibits superior low emissivity; when perovskite photovoltaic modules incorporating conductive Low-E glass 1 are used in the building sector, they effectively block the transfer of heat between indoors and outdoors, providing thermal insulation.

[0058] Compared to existing technologies that first deposit a layer of traditional raw materials, indium tin oxide (ITO) or fluorine-doped tin oxide (FTO), onto glass as a transparent conductive electrode, then fabricate the remaining parts of the perovskite photovoltaic module on the ITO or FTO-plated transparent conductive substrate, and finally combine it with Low-E glass, this embodiment uses conductive Low-E glass 1 directly as the transparent conductive electrode layer of the perovskite photovoltaic module. While fulfilling the original function of the perovskite photovoltaic module, it also combines the advantages of Low-E glass: Firstly, it avoids the instability inherent in simply combining the perovskite photovoltaic module and Low-E glass, and also eliminates the need for depositing indium tin oxide (ITO) or fluorine-doped tin oxide (FTO) on the glass. The process of using FTO (Flat-to-Oxide) reduces the number of steps involved in depositing additional transparent conductive electrodes. Secondly, it eliminates the need for assembly and bonding of Low-E glass with perovskite photovoltaic modules based on materials such as glass-ITO. This not only reduces the number of glass layers, significantly decreasing the module thickness, but also greatly simplifies the process, reducing equipment, raw material, and energy costs, resulting in a significant reduction in the overall module manufacturing cost. Furthermore, since it eliminates the use of indium tin oxide (ITO), a scarce and expensive raw material, as a transparent electrode, it avoids the large-scale use of ITO, significantly reducing the raw material cost of conductive Low-E glass compared to that of indium tin oxide (ITO).

[0059] Specifically, in this embodiment:

[0060] The conductive Low-E glass 1 has a silver-plated layer, which serves as the cell electrode of the perovskite photovoltaic module. As a core functional layer, the silver-plated layer is directly responsible for low-emissivity characteristics, and its sheet resistance is 0.9-2 Ω / sq. All other film layers on the perovskite photovoltaic module, except for the transparent conductive electrode layer, are sequentially stacked based on the silver-plated layer of the conductive Low-E glass 1.

[0061] The conductive Low-E glass 1 glass substrate serves as the conductive electrode substrate for the transparent conductive electrode layer on the perovskite photovoltaic module.

[0062] The conductive Low-E glass 1 also has an intermediate film layer, which is a composite stacked structure of dielectric layer / functional layer. Preferably, the intermediate film layer is a Si3N4 or TiO2 dielectric layer, a ZnO or SnO2 dielectric layer, and an Ag functional layer. The stacking number and material thickness of the dielectric layer and functional layer can be adjusted according to actual needs. The dielectric layer is used to optimize visible light transmittance and color neutrality.

[0063] In one possible embodiment, the composite film structure of the conductive Low-E architectural glass includes, from the glass substrate outwards, the following layers in sequence: ZnOx or TiOx layer, Ag layer, Ti or NiCr layer, ZnOx or SiNx layer, Ag layer, Ti or NiCr layer, ZnOx or SiNx layer, and Ag layer.

[0064] Preferably, the conductive Low-E glass 1 is double-silver or triple-silver Low-E glass. The light transmittance of the conductive Low-E glass 1 is 40%-70%.

[0065] The materials of the first charge transport layer 2 and the second charge transport layer 4 are electron transport layer materials such as SnO2 or hole transport layer materials such as SAMs, NiOx, and PTAA.

[0066] The perovskite layer 3 is made of a perovskite material with adjustable composition, including elements such as Cs, MA, FA, Pb, I, Br, and Cl, which are mixed in a certain proportion. It is prepared by methods such as spin coating, blade coating, and slot coating.

[0067] The materials for buffer layer 5 include BCP, MoOx, SnO2, etc.

[0068] Electrode layer 6 includes opaque metal electrodes such as Ag, Au, and Cu, or flexible transparent conductive film layers including conductive films of metal oxides such as ITO, IWO, and IZO, silver nanowires, and multilayer composite transparent materials such as ITO / Cu / ITO, etc.

[0069] The outer protective layer 7 can be a transparent, weather-resistant polymer film to effectively resist ultraviolet rays, moisture and mechanical damage; or it can be a metal oxide deposited by atomic layer deposition, etc.

[0070] More specifically, when conductive Low-E glass 1 is used as a transparent conductive electrode layer in perovskite photovoltaic modules, it has good compatibility with other functional layers on the perovskite photovoltaic modules, ensuring the stable performance of the entire photovoltaic module and preventing performance degradation over long-term use.

[0071] Based on this, when a self-cleaning glass structure is installed on one side of the perovskite photovoltaic module, a hollow layer is provided between the perovskite photovoltaic module and the self-cleaning glass structure. This results in a multi-layered composite structure of self-cleaning glass + hollow layer + perovskite photovoltaic module, with the self-cleaning glass structure located on the side of the perovskite photovoltaic module away from the conductive Low-E glass 1. Furthermore, the hollow layer is filled with an inert gas to enhance the stability of the perovskite photovoltaic module. In one possible embodiment, when the perovskite photovoltaic module with conductive Low-E glass 1 is used in a triple-glass, two-cavity building application, the perovskite photovoltaic module with conductive Low-E glass 1 can serve as the outermost layer of the building, with a cavity between it and the adjacent building glass. This cavity is filled with an inert gas, such as nitrogen. Combined with the stable performance of the perovskite module with conductive Low-E glass 1, this reduces the potential damage to the module caused by environmental factors and improves stability.

[0072] Example 2

[0073] This embodiment provides a method for preparing the perovskite photovoltaic module in Embodiment 1, including the following steps:

[0074] Step 1) P1 is etched on a conductive Low-E glass substrate using a near-infrared nanosecond or green picosecond laser scribing process, wherein the spacing of the P1 scribing lines is 4-8 mm and the width is 20-50 μm.

[0075] Step 2) Use glass cleaner and deionized water to ultrasonically clean the substrate after P1 etching and then dry it with dry air.

[0076] Step 3) Prepare a nickel oxide hole transport layer (i.e., prepare the first charge transport layer 2) and a passivation layer sequentially, wherein:

[0077] The nickel oxide hole transport layer is prepared by magnetron sputtering or solution method, with a thickness of 5-20 nm, preferably 20 nm. The solution method includes: spin-coating a NiOx dispersion onto a substrate that has been treated with ultraviolet ozone for 10-30 min, preferably 10 min. The spin-coating conditions are: low speed 500-1500 rpm for 3-10 s, high speed 3000-6000 rpm for 30-60 s, annealing at 150-200℃ for 5-30 min, preferably low speed 500 rpm for 3 s, high speed 4000 rpm for 30 s, annealing at 150℃ for 30 min.

[0078] The passivation layer is made of a monolayer material or an organic ammonium salt material. Taking 2PACz monolayer material as an example, when it is prepared by spin coating, the spin coating conditions are as follows: 2PACz material is prepared by spin coating at a low speed of 3000-5000 rpm for 30-60 seconds and then annealed at 90-110℃ for 10-30 minutes. Preferably, 2PACz material is prepared by spin coating at a low speed of 3000 rpm for 30 seconds and then annealed at 100℃ for 10 minutes.

[0079] Step 4) Spin-coat the perovskite pre-solid and anneal to form a perovskite thin film light-absorbing layer (i.e., prepare perovskite layer 3), followed by the preparation of a surface passivation layer, wherein:

[0080] The perovskite precursor solution contains PbI2, FAI, MAI, MACl, PbBr2, and PbCl2, and the solvent is a DMF / NMP mixed system or a DMF / DMSO system. The solution and solvent are mixed and dissolved at room temperature for 1-12 hours, preferably 12 hours, with a concentration of 1.5-1.7 M.

[0081] The spin coating parameters are 2000-5000 rpm, with 100-300 μL of chlorobenzene added dropwise in the last 5-10 seconds. The annealing conditions are 100-150℃ for 5-30 min, preferably 5000 rpm, with 300 μL of chlorobenzene added dropwise in the last 5 seconds, and the annealing conditions are 100℃ for 30 min.

[0082] The surface passivation layer is prepared by spin coating, and the materials are selected from organic salts, 2D materials, and small molecule materials. Taking 2-thiophene ethyl ammonium chloride as an example, the preparation conditions for spin coating are as follows: 2-thiophene ethyl ammonium chloride is prepared by spin coating at a low speed of 3000-5000 rpm for 30-60 seconds and then annealing at 100-130℃ for 3-10 minutes. Preferably, 2-thiophene ethyl ammonium chloride is prepared by spin coating at a low speed of 3000 rpm for 30 seconds and then annealing at 110℃ for 3 minutes.

[0083] Step 5) Preparation of electron transport layer (i.e., preparation of second charge transport layer 4): The electron transport layer is prepared by vacuum thermal deposition of a fullerene C60 layer with a thickness of 10-50 nm, preferably 20 nm, or by solution spin coating of PCBM layer, with spin coating conditions of 5-20 mg / ml, rotation speed of 2500-4000 rpm, time of 30-60 s, annealing at 70-120℃ for 5-30 min, preferably 20 mg / ml, rotation speed of 2500 rpm, time of 30 s, annealing at 100℃ for 10 min.

[0084] Step 6) Prepare the interface buffer layer (i.e., prepare buffer layer 5): The interface buffer layer 5 is a BCP layer with a thickness of 5-20 nm prepared by vacuum deposition or a tin oxide layer with a thickness of 10-50 nm prepared by atomic deposition.

[0085] Step 7) P2 etching is performed using a green picosecond laser scribing process, wherein the distance between the P2 scribing and P1 is 30-100μm and the width is 40-100μm.

[0086] Step 8) Prepare electrode layer 6: including a metal electrode layer and a transparent electrode layer. The metal electrode layer is a 50-200nm Cu layer prepared by magnetron sputtering, preferably 100nm. The transparent electrode layer includes a semi-transparent electrode layer. The semi-transparent electrode is a mixed layer of ITO and Cu with a total thickness of 50-200nm prepared by magnetron sputtering, preferably 100nm, such as an ITO / Cu / ITO stacked structure.

[0087] Step 9) Etch P3 using a green picosecond or ultraviolet picosecond laser scribing process, wherein the distance between the P3 scribing and P2 is 30-100μm and the width is 40-100μm.

[0088] Example 3

[0089] This embodiment illustrates the application of Low-E glass in perovskite photovoltaic modules as described in Embodiments 1 and 2. The conductive Low-E glass is used as a transparent conductive electrode layer in the perovskite photovoltaic module.

[0090] Example 4

[0091] This embodiment illustrates the application of perovskite photovoltaic modules in building integration as described in Embodiments 1 and 2.

[0092] When perovskite photovoltaic modules are integrated into buildings, their appearance can be adjusted according to design requirements, with adjustable color and transparency to blend seamlessly with the overall architectural style. The overall light transmittance of the solar module is achieved by adjusting the film thickness of the perovskite layer, the module's marking design, or the band gap of the perovskite layer; this technology is existing and will not be elaborated upon further here.

[0093] In addition, perovskite photovoltaic modules are flexible and diverse in their installation methods, and can be made into photovoltaic curtain walls, photovoltaic roofs, etc., which not only realizes the self-generation function of buildings, but also enhances the aesthetics and technological feel of buildings.

[0094] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. The application of Low-E glass in perovskite photovoltaic modules, characterized in that, The conductive Low-E glass is used as a transparent conductive electrode layer in perovskite photovoltaic modules.

2. The application of Low-E glass in perovskite photovoltaic modules according to claim 2, characterized in that, The perovskite photovoltaic modules are integrated into building applications.

3. A perovskite photovoltaic module, characterized in that, It includes conductive Low-E glass and a perovskite layer, wherein the conductive Low-E glass and the perovskite layer are compositely disposed, and the conductive Low-E glass serves as a transparent conductive electrode layer of the perovskite photovoltaic module.

4. The perovskite photovoltaic module according to claim 3, characterized in that, The conductive Low-E glass has a silver plating layer, which serves as the battery electrode of the transparent conductive electrode layer on the perovskite photovoltaic module. The sheet resistance of the silver plating layer is 0.9-2 Ω / sq.

5. The perovskite photovoltaic module according to claim 4, characterized in that, The conductive Low-E glass is double-silver or triple-silver Low-E glass, and the light transmittance of the conductive Low-E glass is 40%-70%.

6. The perovskite photovoltaic module according to claim 3, characterized in that, The conductive Low-E glass also has an intermediate film layer; The intermediate film layer is a composite stacked structure of dielectric layer / functional layer, wherein the stacking number and material thickness of the dielectric layer and the functional layer can be adjusted.

7. The perovskite photovoltaic module according to claim 3, characterized in that, The perovskite photovoltaic module further includes a first charge transport layer, a second charge transport layer, a buffer layer, an electrode layer, and an outer protective layer, wherein the conductive Low-E glass, the first charge transport layer, the perovskite layer, the second charge transport layer, the buffer layer, the electrode layer, and the outer protective layer are sequentially stacked and composited.

8. The perovskite photovoltaic module according to claim 3, characterized in that, When a self-cleaning glass structure is provided on one side of the perovskite photovoltaic module, a hollow layer is provided between the perovskite photovoltaic module and the self-cleaning glass structure, and the hollow layer is filled with an inert gas. The self-cleaning glass structure is located on the side of the perovskite photovoltaic module away from the conductive Low-E glass.

9. A method for preparing a perovskite photovoltaic module, used to prepare the perovskite photovoltaic module according to any one of claims 2-8, characterized in that, Includes the following steps: Step 1) P1 etching is performed on a conductive Low-E glass substrate by laser scribing process, wherein the spacing of the P1 scribing lines is 4-8 mm and the width is 20-50 μm. Step 2) Perform ultrasonic cleaning and drying on the substrate after P1 etching; Step 3) Prepare the nickel oxide hole transport layer and passivation layer sequentially; Step 4) Spin-coat the perovskite pre-liquid and anneal to form a perovskite thin film light-absorbing layer, followed by the preparation of a surface passivation layer; Step 5) Prepare the electron transport layer; Step 6) Prepare the interface buffer layer; Step 7) Perform P2 etching using a laser scribing process; Step 8) Prepare the electrode layer; Step 9) Perform P3 etching using a laser scribing process.

10. The method for preparing a perovskite photovoltaic module according to claim 9, characterized in that, In step 2), glass cleaner and deionized water are used for ultrasonic cleaning, and dry air is used for drying.

11. The method for preparing a perovskite photovoltaic module according to claim 9, characterized in that, In step 3), the nickel oxide hole transport layer is prepared by magnetron sputtering or solution method, with a thickness of 5-20 nm. The solution method includes: spin-coating a NiOx dispersion onto a substrate that has been treated with ultraviolet ozone for 10-30 min. The spin-coating conditions are: low speed 500-1500 rpm for 3-10 s, high speed 3000-6000 rpm for 30-60 s, and annealing at 150-200℃ for 5-30 min. The passivation layer is made of monolayer material or organic ammonium salt material. The 2PACz material is prepared by spin coating at a low speed of 3000-5000 rpm for 30-60 seconds and then annealing at 90-110℃ for 10-30 minutes.

12. The method for preparing a perovskite photovoltaic module according to claim 9, characterized in that, In step 4), the perovskite precursor solution contains PbI2, FAI, MAI, MACl, PbBr2, and PbCl2, and the solvent is a DMF / NMP mixed system or a DMF / DMSO system, dissolved at room temperature for 1-12 hours, with a concentration of 1.0-1.7M. The spin coating parameters are 2000-5000 rpm, and 100-300 μL of chlorobenzene is added dropwise in the last 5-10 seconds. The annealing conditions are 100-150℃ for 5-30 min. The surface passivation layer was prepared by spin coating. The materials were selected from organic salts, 2D materials, and small molecule materials. Among them, 2-thiophene ethyl ammonium chloride was prepared by spin coating at a low speed of 3000-5000 rpm for 30-60 seconds and then annealing at 100-130℃ for 3-10 minutes.

13. The method for preparing a perovskite photovoltaic module according to claim 9, characterized in that, In step 5), the electron transport layer is prepared by vacuum thermal deposition of a fullerene C60 layer with a thickness of 10-50 nm, or by solution spin coating of a PCBM layer with spin coating conditions of 5-20 mg / ml, rotation speed of 2500-4000 rpm, time of 30-60 s, and annealing at 70-120℃ for 5-30 min.

14. The method for preparing a perovskite photovoltaic module according to claim 9, characterized in that, In step 6), the interface buffer layer is a BCP layer with a thickness of 5-20 nm prepared by vacuum deposition or a tin oxide layer with a thickness of 10-50 nm prepared by atomic deposition.

15. The method for preparing a perovskite photovoltaic module according to claim 9, characterized in that, In step 8), the metal electrode layer is a 50-200nm Cu layer prepared by magnetron sputtering, wherein the semi-transparent electrode is a mixed layer of ITO and Cu with a total thickness of 50-200nm prepared by magnetron sputtering.

16. The method for preparing a perovskite photovoltaic module according to claim 9, characterized in that, The laser scribing processes in steps 1), 7), and 9) respectively employ near-infrared nanosecond laser / green picosecond laser, green picosecond laser, and green / ultraviolet picosecond laser. The distance between the line P2 and P1 is 30-100μm, and the width is 40-100μm; The distance between the line P3 and P2 is 30-100μm, and the width is 40-100μm.

Citation Information

Patent Citations

  • Novel energy-saving electricity generation glass curtain wall based on transparent perovskite photovoltaic module

    CN108625517A

  • Power generation glass and curtain wall glass based on perovskite photovoltaic module

    CN221807575U